Hypertonic saline protects brain endothelial cells against hypoxia correlated to the levels of estimated glomerular filtration rate and interleukin-1β. Issue 1 (January 2017) - Chen, Sheng-Long; Deng, Yi-Yu; Wang, Qiao-Sheng; Han, Yong-Li; Jiang, Wen-Qiang; Fang, Ming; Hu, Bei; Wu, Zhi-Xin; Huang, Lin-Qiang; Zeng, Hong-Ke
Abstract: Objective: The aim of this study was to verify the protective effect of hypertonic saline (HS) on brain endothelial cells under hypoxic conditions and the relevant underlying mechanism. Methods: bEnd.3 cells were treated with oxygen-glucose deprivation (OGD)-induced injury. To measure HS performance, cell viability was determined using the 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium salt assay, and cell apoptosis was assessed by flow cytometry and Terminal deoxynucleotidyl transferase UTP nick-end labeling staining. RNA-seq was performed to assess the expression profiles and screen the candidate genes that participated in OGD-induced injury and the HS protective effect. Quantitative real-time polymerase chain reaction (qPCR) and western blot analysis were used to confirm the expression of candidate genes, and enzyme-linked immunosorbent assay was used to measure the level of interleukin (IL)-1β. Overexpression analyses were performed to confirm the functions of the differentially expressed genes. Results: HS with a concentration of 40 mmol/L NaCl had an obvious protective effect on bEnd.3 cells after OGD-induced injury, resulting in increased cell viability and a smaller percentage of apoptotic cells. According to the RNA-seq results, epidermal growth factor receptor (EGFR) was chosen as the differentially expressed gene target in this study. The qPCR and western blot analyses further confirmed that the levels of EGFR/phosphorylated epidermal growth factor receptor and IL-1β were enhanced after OGD-induced injury, but attenuated after treatment with 40 mmol/L of NaCl HS. Overexpressed EGFR reversed the protective effect of HS that caused low viability and high rates of apoptosis in cells. Conclusion: HS can protect endothelial cells against OGD-induced injury, but is affected by the expression of EGFR/p-EGFR and IL-1β.